An above IC MEMS RF switch. - Saias, D. (IEEE Journal of solid state circuits)
Addressing reconfiguration of radio frequency (RF) systems might require high performance integrated RF switching capabilities. In this regard, a particular design experience of an integrated circuit (IC) monolithically integrated microelectromechanical systems (MEMS) ohmic switch is reported here. Applications at 2 GHz have been targeted. The MEMS device was processed on top of a 0.25-μm standard BiCMOS wafer including the switch IC driver. An extensive RF characterization has been made. The switch exhibits at 2 GHz a 0.18-dB insertion loss and a 57-dB isolation level. This realization opens the way to further designs of reconfigurable architectures for multiband and multistandard mobile terminals.